2012
DOI: 10.1007/s10144-012-0320-y
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of climatic factors relating to occurrence of the maize orange leafhopper, Cicadulina bipunctata

Abstract: The maize orange leafhopper, Cicadulina bipunctata is a serious pest of forage maize in East and Southeast Asia. In temperate Japan, the occurrence of this leafhopper fluctuates widely among years. Here, we examined effects of climatic factors (temperature, precipitation and sunlight) on the occurrence of C. bipunctata. Seasonal occurrence of adult C. bipunctata in a census field from July to August, when forage maize was most susceptible to the pest, could be described by a simple exponential function with tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…The recent rapid expansion of the distribution of C. bipunctata is thought to be caused by global warming 17,20 . We examined the effects of climatic factors (temperature, precipitation and sunlight) on the occurrence of C. bipunctata, using field data from 2004 to 2010 in Kumamoto Prefecture 17 .…”
Section: Recent Outbreak Of C Bipunctatamentioning
confidence: 99%
See 1 more Smart Citation
“…The recent rapid expansion of the distribution of C. bipunctata is thought to be caused by global warming 17,20 . We examined the effects of climatic factors (temperature, precipitation and sunlight) on the occurrence of C. bipunctata, using field data from 2004 to 2010 in Kumamoto Prefecture 17 .…”
Section: Recent Outbreak Of C Bipunctatamentioning
confidence: 99%
“…We examined the effects of climatic factors (temperature, precipitation and sunlight) on the occurrence of C. bipunctata, using field data from 2004 to 2010 in Kumamoto Prefecture 17 . The results of a multiple linear regression analysis indicated the increased occurrence of adult C. bipunctata due to higher temperatures during both the previous winter and early summer of the current year.…”
Section: Recent Outbreak Of C Bipunctatamentioning
confidence: 99%
“…In fact, expansion of the distribution of C. bipunctata in Kyushu probably started in the late 1980s , when global warming became conspicuous (Collins et al 2013). In addition, abundance of C. bipunctata in Japan is influenced positively by both winter and early summer temperatures (Matsukura et al 2012b), and the reproductive rate of C. bipunctata is maximized at a higher temperature (31°C) than in most common leafhoppers in temperate Japan (Tokuda and Matsumura 2005;Kiritani 2012). These facts suggest that global warming facilitated expansion of the range of C. bipunctata in temperate Japan.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, the cumulative low temperature during winter in each grid square was adopted as an indicator of low temperature for our analysis. Risk of MWES occurrence in each grid square was then assessed based on an estimation model of C. bipunctata distribution during summer (Matsukura et al 2012b) and levels of economic injury to forage maize caused by MWES (Matsukura et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Because C. bipunctata has a certain degree of tolerance to high temperatures, such as 31 and 34°C (Tokuda and Matsumura 2005), the expansion of distribution range following global warming is of concern for this species (Matsumura et al 2005;Matsukura et al 2009aMatsukura et al , 2012b. Cicadulina bipunctata occurs in the southern parts and middle-western parts of Kyushu (Webb 1987;Matsukura et al 2009a), and our most recent study revealed that the leafhopper is also distributed in the middle-eastern parts, but not in the northern parts, of Kyushu (Kumashiro et al 2012).…”
Section: Introductionmentioning
confidence: 99%